Dampak Pengetahuan, Motivasi, dan Kondisi Lingkungan Keluarga Terhadap Ketertarikan Mahasiswa dalam Berwirausaha - Ni Kadek Tari Maya Pertiwi; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2026)
This study aims to analyze the influence of entrepreneurial knowledge, entrepreneurial motivation, and family environment on accounting students' interest in entrepreneurship. The dependent variable in this research is entrepreneurial interest (Y), while the independent variables consist of entrepreneurial knowledge (X1), entrepreneurial motivation (X2), and family environment (X3). The population in this study includes 289 accounting students from the 2021 and 2022 cohorts. The sampling technique used the Slovin formula with a 10% margin of error, resulting in a sample of 74 respondents. Data were collected through the distribution of questionnaires. The data analysis technique employed is multiple linear regression. The results show that entrepreneurial knowledge (X1) has a significant influence on accounting students' interest in entrepreneurship, entrepreneurial motivation (X2) does not have a significant influence, while the family environment (X3) does have a significant influence on entrepreneurial interest. This study implies that educational institutions and families play a crucial role in fostering the entrepreneurial spirit among students, particularly accounting students